Kinetic study on the crystallization of sodium lead borate glass by differential thermal analyzer [compact disc] - 318240 Ku Mohamad Halmie Ku Halim (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2006